Thematic analysis, thinking, al-Ghazali - Ruslan, Ruslan (FAKULTAS TARBIYAH, 2023)
This paper examines further al-Ghazali's thoughts for the development of the Islamic world. The aim is to find common threads about al-Ghazali's thoughts regarding the science of Uhuluddin. Apart from that, to examine the discipline of Uhuluddin, which is a branch of knowledge in Islamic religious studies, by focusing attention on the contribution of educational thought adapted to the current context and the implications of his thought in the context of life in Muslim society. The method used in this paper is descriptive analysis, namely by analyzing al-Ghazali's thoughts according to the context of Ushuluddin's science. The analysis used is thematic analysis which aims to analyze al-Ghazali's thoughts in Ushuluddin science. The results of the research show that there is a Basic Understanding of Uhuluddin Science, Al-Ghazali's Contribution to Uhuluddin Science, Al-Ghazali's Influence in the Development of Uhuluddin Science, the Relevance of Al-Ghazali's Thoughts in the Modern Context, and the practical implications of Al-Ghazali's thoughts in Uhuluddin Science, both in terms of religious education, theology, or its relevance in solving contemporary problems in Muslim society.